Study on air-cushion tracked vehicle performance: theoretical analysis and experimental validation - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Aminanda, Yulfian (2011)
This paper presents a theoretical framework for simulating the vehicle ground contact pressure distribution, vehicle sinkage and the tractive performance of an air-cushion tracked vehicle. It takes into account track sizes of the vehicle, air-cushion effective area as well as the terrain nominal pressure and vehicle sinkage. The subsequent validation of the theoretical method by means of quarter-scale test made with an air-cushion tracked vehicle is described. Several experiments have been conducted to investigate the tractive performance of the vehicle. Experiment and simulation results show that the optimal load distribution from the vehicle to the air-cushion system can be obtained by using the developed model with the slippage of 15% and tractive efficiency of 56 % based on terramechanics.